Teaching Adult English Language Learners Through English Song Lyrics Gap-Fill at STIT Tanggamus - Pradana, Sandi (LinguaScopes: International Journal of Language Education, 2024)
This study evaluates the effectiveness of gap-fill activities employing English song lyrics in boosting listening skills, vocabulary acquisition, and motivation among adult learners at STIT Tanggamus. Utilizing a qualitative case study technique, the research collects data through classroom observations, semi-structured interviews, and questionnaires to measure learners’ involvement and impressions of this novel teaching style. The findings demonstrate that integrating familiar songs dramatically enhances learners’ language skills and confidence while promoting a collaborative and joyful learning environment. However, problems such as picking good music and handling initial learner concern underline the necessity for careful implementation. The study suggests that song-based activities can be a valuable instrument in adult language education, bringing practical insights for curriculum creation and teaching practices.